PENINGKATANPERILAKU MORAL MELALUI PEMBELAJARAN HADIST ANAK USIA 5-6 TAHUN RA DHARMA WANITA PERSATUAN KEMENAG PONTIANAK - Nuryani, Sri; Syukri, M.; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractEnhancing moral behavior through hadith learning is a way to improve children's moral behavior by using a hadith that is delivered using audio-visual media. In this case the researcher wants to see and examine how teachers improve and plan learning through hadith learning that utilizes audio-visual media as a source of learning in children aged 5-6 years. The purpose of this study is to describe the planning of hadith learning, how the implementation of hadith learning and the improvement of moral behavior in children through the learning of hadith children aged 5-6 years at RA DWP Regional Office of Ministry of Religion in Pontianak. This research was conducted using descriptive methods by conducting class action research, the research data are presented in the form of words and numbers. As for the source of the data is group B children aged 5-6 years, totaling 34 people. Data collection techniques used in this study were non-test techniques. While the data collection tool is in the form of direct observation. From the results of researchers show that the learning model through hadith learning has been going well and implemented in accordance with the RPPH that was made. In real media learning that researchers have prepared in accordance with the themes and development of children aged 5-6 years in RA DWP Pontianak Regional Office of Ministry of Religion. Starting from the results of the study, then there are a number of suggestions given namely relating to (1) the media used, (2) classroom settings, (3) plans in learning.Â Keywords: Behavior, Hadith, Moral